2015
DOI: 10.3389/fmicb.2015.01025
|View full text |Cite
|
Sign up to set email alerts
|

Exploring antibiotic resistance genes and metal resistance genes in plasmid metagenomes from wastewater treatment plants

Abstract: Plasmids operate as independent genetic elements in microorganism communities. Through horizontal gene transfer (HGT), they can provide their host microorganisms with important functions such as antibiotic resistance and heavy metal resistance. In this study, six metagenomic libraries were constructed with plasmid DNA extracted from influent, activated sludge (AS) and digested sludge (DS) of two wastewater treatment plants (WWTPs). Compared with the metagenomes of the total DNA extracted from the same sectors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
72
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(82 citation statements)
references
References 53 publications
8
72
0
2
Order By: Relevance
“…Resistance gene clusters 1 and 2 are shown expanded in grey. b Circular distribution of antimicrobial resistance genes by class, and abundance in total annotated antimicrobial genes found six plasmid metagenomes from the influent and sludge from two wastewater treatment plants (modified and reproduced with permission from [192]) …”
Section: Antimicrobial Resistance In Bovine Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance gene clusters 1 and 2 are shown expanded in grey. b Circular distribution of antimicrobial resistance genes by class, and abundance in total annotated antimicrobial genes found six plasmid metagenomes from the influent and sludge from two wastewater treatment plants (modified and reproduced with permission from [192]) …”
Section: Antimicrobial Resistance In Bovine Pathogensmentioning
confidence: 99%
“…The authors also detected MGEs in tannery DNA samples, but limitations in methodology restricted investigating linkages with AMR genes. Taking a similar approach, Li et al [192] examined the resistome of plasmids harvested from influent, activated sludge, and digested sludge of two Hong Kong wastewater treatment plants receiving domestic and slaughterhouse (cattle and other production animals) sewage. AMR genes were detected in all of the plasmid metagenomes: the most abundant were tetracycline resistance genes (29% of all AMR gene sequences), quinolone resistance genes (17%), and β-lactam resistance genes (12%) [192].…”
Section: The Bovine Resistome and The Wider Environmentmentioning
confidence: 99%
“…Therefore, microbial communities in WWTP exist as model systems to explore various plasmids carrying genes with important functions for their hosts, including antibiotic resistance, pathogenicity, virulence, biodegradation, and heavy metal resistance (Li et al, 2015). Several studies have reported the presence of immense varieties of plasmids containing antibiotic resistance genes in WWTP (Li et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial adaptation mechanisms in environment are metal sorption, accumulation and uptake, mineralization, precipitation, efflux from the cell, oxidation or reduction to less toxic or nontoxic forms (Nies 1999). Genes encoding proteins involved in the mechanisms of biotransformation of toxic heavy metals to less toxic forms are often present on circular plasmid DNA which may be involved in the processes of horizontal gene transfer (Li et al 2015). Heavy -metal tolerant bacterial strains could be used in bioremediation but before their real incorporation into the real processes we must get as much information about these strains.…”
Section: Introductionmentioning
confidence: 99%